Multi-Criteria Evaluation of Land Cover Policies Using Fuzzy AHP and Fuzzy ANP: The Case of Turkey - Demirel, Tufan; Musdal, Hande; Demirel, Nihan Cetin; Yucenur, G. Nilay (TAYLOR & FRANCIS INC, 2009)
Land cover and use strategies have gained importance with decreases in per capita availability of land worldwide. The food deficit is increasing as a result of increases in the population, more so in developing and under-developed countries. A multi-criteria decision-making method using fuzzy Analytic Hierarchy Process (AHP) and fuzzy Analytic Network Process (ANP) for the evaluation of alternate land cover policies under various confidence levels of the decision-makers has been proposed. Computations have been done by using fuzzy AHP in terms of reflection ambiguity and uncertainty of the real world. Comparisons were made with the results obtained by using fuzzy ANP.
Keywords: land cover policies; agriculture; fuzzy analytic hierarchy process; fuzzy analytic network process; ANALYTIC NETWORK PROCESS; EXTENT ANALYSIS METHOD; SELECTION; REGION; Biodiversity & Conservation; Environmental Sciences & Ecology